Decoupled and coupled moons' ephemerides estimation strategies application to the JUICE mission. (15th September 2022) - Fayolle, M.; Dirkx, D.; Lainey, V.; Gurvits, L.I.; Visser, P.N.A.M.
Abstract: When reconstructing natural satellites' ephemerides from space missions' tracking data, the dynamics of the spacecraft and natural bodies are often solved for separately, in a decoupled manner. Alternatively, the ephemeris generation and spacecraft orbit determination can be performed concurrently. This method directly maps the available data set to the estimated parameters' covariances while fully accounting for all dynamical couplings. It thus provides a statistically consistent solution to the estimation problem, whereas this is not directly ensured with the decoupled strategy. For the Galilean moons in particular, the JUICE mission provides a unique, although challenging, opportunity for ephemerides improvement. For such a dynamically coupled problem, choosing between the two state estimation strategies will be influential. This paper quantifies the Galilean moons' state uncertainties attainable when applying a coupled estimation strategy to simulated JUICE data, and discusses the challenges that remain to be addressed to achieve such a coupled solution from real observations. We first provide a detailed, explicit formulation for the coupled approach, which was still missing in the literature although already used in past studies. We then assessed the relative performances of the two ephemerides generation techniques for the JUICE test case. To this end, we used both decoupled and coupled models on simulated JUICE radiometric data. We compared the resulting covariances for the Galilean moons' states, and showed that the decoupled approach yields slightly lower formal errors for the moons' tangential positions. However, the coupled model can reduce the state uncertainties by more than one order of magnitude in the radial direction ( i.e. towards the central body). It also proved more sensitive to the dynamical coupling between Io, Europa and Ganymede, allowing the state solutions for the first two moons to fully benefit from JUICE orbital phase around Ganymede. On the other hand, we showed that the choice of state estimation methods does not strongly affect the moons' gravity field determination. Many issues still remain to be solved before a concurrent estimation strategy can be successfully applied, especially to reconstruct the moons' dynamics over long timescales. Nonetheless, our analysis highlights promising ephemerides improvements and thus motivates future efforts to reach a coupled state solution for the Galilean moons.